Implementasi Antarmuka Website Responsif Menggunakan Framework Roots Sage Dan Tailwind Css Pada Website Kajianmu - Muhamad Bintang Rukmana; Adrian Reza (Riset Sinergi Indonesia (RISINDO), 2026)
This research specifically discusses the stages and implementation process of the user interface (front-end) section applied to the Kajianmu website, a digital information platform. The main goal of this development activity is to be able to create a website interface that is not only visually modern, but also systematically structured, and has a high level of responsiveness to ensure content can be accessed comfortably and optimally through various types of user devices. The entire technical development process is carried out by modernizing the basic architecture of the WordPress theme by utilizing the Sage Roots framework. The use of this tool allows the implementation of the Laravel Blade template engine feature, which functions to create a much more modular, organized, and neat program code structure. In addition, Tailwind CSS technology is also intensively used as a styling framework that prioritizes utility to help speed up the interface creation process so that the results are precise and in accordance with the design that has been created. This development approach is implemented to replace traditional conventional theme development methods, with a primary focus on aspects of efficiency in writing code and precision of interface details. The final results of this study show evidence that the implementation of modern technology has succeeded in producing the Kajianmu website with a component structure that is very easy to manage (maintain), and displays a consistent visual appearance (pixel-perfect) both when opened on desktop screens and mobile devices.